2005
DOI: 10.1091/mbc.e04-10-0919
|View full text |Cite
|
Sign up to set email alerts
|

Basal Body Duplication and Maintenance Require One Member of theTetrahymena thermophilaCentrin Gene Family

Abstract: Centrins, small calcium binding EF-hand proteins, function in the duplication of a variety of microtubule organizing centers. These include centrioles in humans, basal bodies in green algae, and spindle pole bodies in yeast. The ciliate Tetrahymena thermophila contains at least four centrin genes as determined by sequence homology, and these have distinct localization and expression patterns. CEN1's role at the basal body was examined more closely. The Cen1 protein localizes primarily to two locations: one is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
131
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(142 citation statements)
references
References 60 publications
10
131
1
Order By: Relevance
“…Several further discrete localisations have also been identified, in cilia (Gonda et al, 2004;Guerra et al, 2003;LeDizet and Piperno, 1995) and ciliary-derived organelles of sensory cells (Giessl et al, 2006), at the contractile vacuole pores in Tetrahymena (Stemm-Wolf et al, 2005) and at the Golgi in Trypanosoma (He et al, 2005;Selvapandiyan et al, 2007). Interestingly, if species differ widely in their number of centrin genes (one in yeast, four in mammals, seven in Leishmania, at least ten in Tetrahymena and 49 in Paramecium), when more than a single gene is present, a particular localisation or function may involve either a single or different centrin isotypes and conversely, a particular isotype may show different localisations or functions.…”
Section: +mentioning
confidence: 94%
See 1 more Smart Citation
“…Several further discrete localisations have also been identified, in cilia (Gonda et al, 2004;Guerra et al, 2003;LeDizet and Piperno, 1995) and ciliary-derived organelles of sensory cells (Giessl et al, 2006), at the contractile vacuole pores in Tetrahymena (Stemm-Wolf et al, 2005) and at the Golgi in Trypanosoma (He et al, 2005;Selvapandiyan et al, 2007). Interestingly, if species differ widely in their number of centrin genes (one in yeast, four in mammals, seven in Leishmania, at least ten in Tetrahymena and 49 in Paramecium), when more than a single gene is present, a particular localisation or function may involve either a single or different centrin isotypes and conversely, a particular isotype may show different localisations or functions.…”
Section: +mentioning
confidence: 94%
“…They have long been shown to localise at two major sites: microtubule organising centres (MTOCs), for example, spindle pole bodies, centrosomes or basal bodies and MTOC-associated arrays of contractile fibres where they were first identified (Salisbury et al, 1984). In MTOCs, centrin is a cytologically discrete and functionally important component, required for their duplication, segregation and positioning (Baum et al, 1986;Koblenz et al, 2003;Paoletti et al, 1996;Ruiz et al, 2005;Salisbury et al, 2002;Stemm-Wolf et al, 2005;Wright et al, 1989;Wright et al, 1985). Remarkably, in acentriolar organisms, which form basal bodies only at a specific stage of their life cycle, such as in Naegleria or Marsilea, centrin synthesis strictly correlates with assembly of basal bodies (Klink and Wolniak, 2001;Levy et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Mammalian centrin-2 is considered the orthologue of the S. cerevisiae Cdc31 gene product, which is clearly required for SPB duplication [141]. Likewise, centrins are essential for the formation of basal bodies in ciliates [142,143]. Whether or not centrin-2 is required for centrosome duplication in human cells is controversial, but there is no question that this protein is a genuine component of vertebrate centrosomes [144][145][146][147].…”
Section: Centrosomes As Signalling Platforms In Vertebrates? (A) Cellmentioning
confidence: 99%
“…Once two strains of different mating types were constructed, they were mated and the subsequent progeny lacked ETU1 in the macronucleus (somatic nucleus), thus creating the etu1D strain. Staining of basal bodies using centrin 1 (Cen1), a basal body marker (Stemm-Wolf et al, 2005), revealed a decrease in the basal body density within cortical rows upon removal of the ETU1 gene product (supplementary material Fig. S3A-C).…”
Section: E-tubulin Is An Essential Protein In Tetrahymena Thermophilamentioning
confidence: 99%
“…All primary antibodies were diluted in 1% BSA in phosphate buffered saline (PBS). The Tetrahymena Cen1 antibody (Stemm-Wolf et al, 2005) was diluted 1:2000. The monoclonal Atu1 antibody (provided by Joe Frankel, University of Iowa, Iowa City, IA) was diluted 1:50.…”
Section: Immunofluorescence Microscopymentioning
confidence: 99%